2014
DOI: 10.1128/aac.02163-13
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Echinocandin MICs against Candida Species in a Multicenter Study of Hospitals That Routinely Perform Susceptibility Testing of Bloodstream Isolates

Abstract: Reference broth microdilution methods of Candida echinocandin susceptibility testing are limited by interlaboratory variability in caspofungin MICs. Recently revised Clinical and Laboratory Standards Institute (CLSI) breakpoint MICs for echinocandin nonsusceptibility may not be valid for commercial tests employed in hospital laboratories. Indeed, there are limited echinocandin susceptibility testing data from hospital laboratories. We conducted a multicenter retrospective study of 9 U.S., Australian, and New Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 17 publications
6
51
2
2
Order By: Relevance
“…The C. albicans isolate was found to harbor a point mutation (S645F) in HS1 of fks1, whereas the C. guilliermondii isolate (except for a constitutive polymorphism) and the C. krusei isolate were wild type for the fks gene; of note, the C. guilliermondii isolate showed an intermediate phenotype for susceptibility to caspofungin and anidulafungin (Table 3). It was noticed that adoption of the revised CLSI CBPs for caspofungin may overstate the rates at which isolates are nonsusceptible (especially intermediate) to caspofungin among C. glabrata and C. krusei isolates (18), and the interlaboratory variability in caspofungin MICs for C. albicans, C. glabrata, C. tropicalis, and C. krusei may considerably limit the use of both the CLSI and EUCAST reference methods (42). Thus, while clinical microbiology laboratories should use micafungin or anidulafungin as a surrogate marker to predict caspofungin susceptibility (43,44), the use of SYO assays was recently advised for hospitals that routinely perform echinocandin susceptibility testing of bloodstream isolates (18).…”
Section: Resultsmentioning
confidence: 99%
“…The C. albicans isolate was found to harbor a point mutation (S645F) in HS1 of fks1, whereas the C. guilliermondii isolate (except for a constitutive polymorphism) and the C. krusei isolate were wild type for the fks gene; of note, the C. guilliermondii isolate showed an intermediate phenotype for susceptibility to caspofungin and anidulafungin (Table 3). It was noticed that adoption of the revised CLSI CBPs for caspofungin may overstate the rates at which isolates are nonsusceptible (especially intermediate) to caspofungin among C. glabrata and C. krusei isolates (18), and the interlaboratory variability in caspofungin MICs for C. albicans, C. glabrata, C. tropicalis, and C. krusei may considerably limit the use of both the CLSI and EUCAST reference methods (42). Thus, while clinical microbiology laboratories should use micafungin or anidulafungin as a surrogate marker to predict caspofungin susceptibility (43,44), the use of SYO assays was recently advised for hospitals that routinely perform echinocandin susceptibility testing of bloodstream isolates (18).…”
Section: Resultsmentioning
confidence: 99%
“…Although this variability can be observed among different species, the differences are most pronounced with C. glabrata and C. krusei (1,2,12). The issue of variable caspofungin MICs is important to address because of the lowering of the CLSI clinical breakpoints for the echinocandins against most Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…The CLSI further suggested that either micafungin or anidulafungin MIC CBPs can be used as predictors of susceptibility or resistance of Candida species to caspofungin. assays in hospitals may reduce the interlaboratory variability in caspofungin MICs against Candida species (28). Among the 14 patients with candidemia due to fluconazoleresistant Candida species, half of the patients had previous exposure to fluconazole.…”
Section: Discussionmentioning
confidence: 99%